Phenotypic Features of Ukerewe and Bunda Indigenous Cattle Populations in the Lake Victoria Basin, Tanzania - G.L. Chasama; E.P. Chang’a (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
The objective of this study was to investigate if the cattle in Ukerewe District represent a strain different from the TSZ strain in Bunda District. Efficient utilization of Tanzania Shorthorn Zebu (TSZ) cattle populations depends on accurate knowledge of their unique characteristics that differentiate them from other populations. Knowledge of morphometric variation is useful for making inferences about farmers’ roles in the evolution of TSZ cattle morphological diversity, landscape fitness and adaptation. Lake Victoria Basin in Tanzania forms an extensive area endowed with a large number of Zebu cattle, but only two strains from the area, namely Tarime and Sukuma cattle, are described. The study aimed to compare body colour and morphometric characteristics of Indigenous cattle populations in the Ukerewe and Bunda districts in Tanzania’s Lake Victoria basin area. A total of 169 adult cattle selected randomly from the study area were examined for colour and morphometric characteristics and then taken linear body measurements. The majority of the cattle had plain colour patterns (63.8% in Ukerewe and 67.4% in Bunda). Predominant coat colours in Ukerewe and Bunda Districts were black and brown, respectively. Around 73% and 87.6% of cattle in the study area had small-sized dewlaps and navel flaps, respectively. All measurements were positively and highly (P < 0.01) correlated with the body weight estimated from heart girth, except for ear length and muzzle circumference. Thus, the strains under the study differed remarkably in phenotype. Genetic characterisation of the strains using molecular techniques is recommended in order to establish if they could have a common origin. There is a need to undertake advanced characterisation with a closer look at the differences highlighted in this study. That will need the use of more sensitive tools so as to analyse the differences more precisely. Genetic characterisation involving the use of molecular techniques is recommended in order to establish if they could have a common origin.